Analysis of Accelerometer Signals for Monitoring of Physical Activity – Methods and Application Results - Poderys, J.; Buliuolis, A.; Grunovas, A.; Vainoras, A.; Ruseckas, R. (Elektronika ir Elektrotechnika, 2009)
The aim was to present the developed system designed for monitoring of physical activity and analysis of accelerometric signals and present the results of applications of the system while various loco motions performed. The participants after warm-up at stadium and at cross-country place performed three tasks i.e. slow walk, brisk walk and jogging. The accelerometers measurements and calculation of integrated acceleration curves from the anteroposterior, mediolateral and vertical directions was an indicator of physical activity level. The results of the study showed that such analysis allowed to define and distinguish allowed to identify physical activity levels across the various intensities investigated at the stadium and at the cross-country conditions when the locomotion compounds more turns, swings and other unexpected movements. Ill. 2, bibl. 12 (in English; summaries in English, Russian and Lithuanian).